2012
DOI: 10.1172/jci60862
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cell vaccination overcomes defective cross-presentation of fungal antigens in a mouse model of chronic granulomatous disease

Abstract: Aspergillus fumigatus is a model fungal pathogen and a common cause of infection in individuals with the primary immunodeficiency chronic granulomatous disease (CGD). Although primarily considered a deficiency of innate immunity, CGD is also linked to dysfunctional T cell reactivity. Both CD4 + and CD8 + T cells mediate vaccine-induced protection from experimental aspergillosis, but the molecular mechanisms leading to the generation of protective immunity and whether these mechanisms are dysregulated in indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 64 publications
2
70
0
1
Order By: Relevance
“…The authors propose a direct role for the autophagosome itself as a compartment for cross-presentation (Li et al, 2011a). The notion that autophagy facilitates cross-presentation is supported by the observation that the autophagy machinery promotes the transit of Aspergillus conidia associated antigen from the early endosome to a Rab14+ cross-presenting compartment (De Luca et al, 2012). Therefore, the role of autophagy in cross-presentation remains to be further explored in detail.…”
Section: Mhci Cross-presentation and Autophagymentioning
confidence: 98%
“…The authors propose a direct role for the autophagosome itself as a compartment for cross-presentation (Li et al, 2011a). The notion that autophagy facilitates cross-presentation is supported by the observation that the autophagy machinery promotes the transit of Aspergillus conidia associated antigen from the early endosome to a Rab14+ cross-presenting compartment (De Luca et al, 2012). Therefore, the role of autophagy in cross-presentation remains to be further explored in detail.…”
Section: Mhci Cross-presentation and Autophagymentioning
confidence: 98%
“…Indeed, the very notion that autophagy partakes in cross-presentation is controversial. While it has been suggested by some studies to play a role, [8][9][10] others have concluded that cross-presentation is autophagy-independent. 11 Resolving this is important given the therapeutic potential of targeting cross-presentation with drugs that manipulate autophagy.…”
Section: Introductionmentioning
confidence: 98%
“…Recognition of conidia by CD8 + T cells required TLR3 and TIR domain-containing adapter-inducing interferon-b (TRIF). On the other hand, MyD88 and TLR6 were necessary for the action of one of the soluble antigens, and other soluble antigens had distinct TLR requirements for driving CD4 + T cell activation (13). This work highlights the complexity of antigen recognition at the level of PRRs.…”
Section: Pattern Recognition Receptors Dictate the Antigen Presentatimentioning
confidence: 81%
“…They found that in wildtype mice, CD8 + T cells are essential for protection upon vaccination with conidia, whereas immunization with soluble Aspergillus proteins admixed with CpG confers protection in a CD4 + T cell-dependent manner (13). The finding that CD8 + T cells are the mediators of protection following immunization with conidia is somewhat surprising in light of previous work reporting that exposure to these fungal elements in primary infection induces a pronounced CD4 + T cell differentiation (4).…”
Section: Divergence Of Antigen Presentation Pathways In Vaccine-inducmentioning
confidence: 99%
See 1 more Smart Citation